A Qualitative Study of Home Health Aides' Perspectives towards COVID-19 Vaccination. (April 2023) - Russell, David; Onorato, Nicole; Stern, Alexis; Vergez, Sasha; Oberlink, Mia; Luebke, Matthew; Feldman, Penny H.; McDonald, Margaret V.; Sterling, Madeline R.
Home health aides provide care to homebound older adults and those with chronic conditions. Aides were less likely to receive COVID-19 vaccines when they became available. We examined aides' perspectives towards COVID-19 vaccination. Qualitative interviews were conducted with 56 home health aides at a large not-for-profit home care agency in New York City. Results suggested that aides' vaccination decisions were shaped by (1) information sources, beliefs, their health, and experiences providing care during COVID-19; (2) perceived susceptibility and severity of COVID-19; (3) perceived benefits of vaccination including protection from COVID-19, respect from colleagues and patients, and fulfillment of work-related requirements; (4) perceived barriers to vaccination including concerns about safety, efficacy, and side effects; and (5) cues to action including access to vaccination sites/appointments, vaccination mandates, question and answer sessions from trusted sources, and testimonials. Providing tailored information with support to address vaccination barriers could lead to improved vaccine uptake.